Exploring the Impact of Educational Administration Knowledge and Work Motivation on the Leadership Effectiveness of Madrasah Heads - Machdum Bachtiar; Isak Iskandar; Anis Fauzi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the positive relationship between educational administrative knowledge, work motivation, and leadership effectiveness among heads of madrasahs. Employing a quantitative correlational survey method, the research targeted 195 heads of MTs. Private in Serang Regency, with a sample size of 30 heads (16% of the population). Instrument reliability was confirmed with Cronbach's alpha values of 0.938 for leadership effectiveness, 0.89 for educational administrative knowledge, and 0.94 for work motivation. Data analysis utilized correlation and regression formulas. The findings revealed a significant positive relationship between educational administrative knowledge (X1) and leadership effectiveness (Y), represented by the regression equation Ŷ = 35.22 + 3X1, with a correlation coefficient of 0.998 at α = 0.05. Additionally, a significant positive relationship was found between work motivation (X2) and leadership effectiveness (Y), described by the regression equation Ŷ = -33.011 + 1.30X2, with a correlation coefficient of 0.999 at α = 0.05. Furthermore, the combined analysis showed a significant positive relationship between educational administrative knowledge (X1) and work motivation (X2) with leadership effectiveness (Y), represented by the equation Ŷ = 3.62 + 1.74X1 + 0.58X2, with a correlation coefficient value of Ry12 = 0.984. These results underscore the importance of educational administrative knowledge and work motivation in enhancing leadership effectiveness among madrasah heads, suggesting that targeted professional development in these areas could significantly improve leadership performance in educational institutions.